Analisis Bibliometrik Muslim Travel: Publikasi Ilmiah di Negara-Negara Seluruh Dunia - Ramadhan, Mochammad Givary; Maika, M. Ruslianor (Jurnal Master Pariwisata (JUMPA), 2022)
This study aims to determine the development map of research related to "Muslim Travel". This research was conducted by searching through the Scopus database. The researcher uses the keyword "Muslim Travel" to generate searches to be more specific with the categories Article title, Abstract, Keywords. In this study, the researcher used a quantitative descriptive method with bibliometric analysis. Based on the search results, the researchers obtained 649 scientific work search results which were then limited to using only two types of article documents and conference papers and then produced 416 documents which were then exported in BibTex format and processed using R-Packages and WebInterface Biblioshiny software, In this study featuring Thematic Maps, on Thematic Maps researchers found that the keyword that appeared most associated with Muslim travel was Human followed by Female. Keywords: Muslim Travel, Biblioshiny, Scopus.